2010
DOI: 10.1016/j.str.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Free State Conformational Sampling of the SAM-I Riboswitch Aptamer Domain

Abstract: Summary Riboswitches are highly structured elements residing in the 5' untranslated region of messenger RNAs that specifically bind cellular metabolites to alter gene expression. While there are many structures of ligand bound riboswitches that reveal details of bimolecular recognition, their unliganded structures remain poorly characterized. Characterizing the molecular details of the unliganded state is crucial for understanding the riboswitch's mechanism of action because it is this state that actively inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
241
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(276 citation statements)
references
References 58 publications
(75 reference statements)
27
241
3
Order By: Relevance
“…48 In addition, Mg 2+ binding induces the P2-P3 helical stacking as well as a close juxtaposition between helices P1 and P3, 23 the latter being consistent with SAXS experiments. 27,53 Disruption of the pseudoknot interaction was found to perturb P1-P3 close juxtaposition, which supports the idea that the pseudoknot may be used as a lever to correctly position P3 close to P1, via the P2-P3 helical stacking (Fig. 3A).…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 71%
See 4 more Smart Citations
“…48 In addition, Mg 2+ binding induces the P2-P3 helical stacking as well as a close juxtaposition between helices P1 and P3, 23 the latter being consistent with SAXS experiments. 27,53 Disruption of the pseudoknot interaction was found to perturb P1-P3 close juxtaposition, which supports the idea that the pseudoknot may be used as a lever to correctly position P3 close to P1, via the P2-P3 helical stacking (Fig. 3A).…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 71%
“…3A), consistent with recent findings obtained by the Batey group. 27 In particular, we have found that the binding of each cofactor is important for the formation of one of the two helical stacks observed in the crystal structure.…”
Section: S-adenosylmethionine (Sam) Riboswitchesmentioning
confidence: 84%
See 3 more Smart Citations